Dynamics of random coupled structures through the wave finite element method. Issue 7 (5th October 2015) - Ben Souf, Mohamed Amine; Ichchou, Mohamed; Bareille, Olivier; Bouhaddi, Noureddine; Haddar, Mohamed
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to develop a new formulation using spectral approach, which can predict the wave behavior to uncertain parameters in mid and high frequencies. Design/methodology/approach – The work presented is based on a hybridization of a spectral method called the "wave finite element (WFE)" method and a non-intrusive probabilistic approach called the "polynomial chaos expansion (PCE)." The WFE formulation for coupled structures is detailed in this paper. The direct connection with the conventional finite element method allows to identify the diffusion relation for a straight waveguide containing a mechanical or geometric discontinuity. Knowing that the uncertainties play a fundamental role in mid and high frequencies, the PCE is applied to identify uncertainty propagation in periodic structures with periodic uncertain parameters. The approach proposed allows the evaluation of the dispersion of kinematic and energetic parameters. Findings – The authors have found that even though this approach was originally designed to deal with uncertainty propagation in structures it can be competitive with its low time consumption. The Latin Hypercube Sampling (LHS) is also employed to minimize CPU time. Originality/value – The approach proposed is quite new and very simple to apply to any periodic structures containing variabilities in its mechanical parameters. The Stochastic Wave Finite Element can predict the dynamic behavior from wave sensitivity of any uncertain media. The approach presented is validated for two different cases: coupled waveguides with and without section modes. The presented results are verified vs Monte Carlo simulations.